1952
DOI: 10.1039/jr9520003977
|View full text |Cite
|
Sign up to set email alerts
|

762. Griseofulvin. Part IV. Structure

Abstract: The structure 7-chloro-4 : 6-dimethoxycoumaran-3-one-2-s~iro-l'-(2'methoxy-6'-methylcycZohex-2'-en-4'-one) (IX ; R = Me) accounts for the known physical and chemical properties of griseofulvin and for the degradation products described in Parts 1-111 (preceding papers). FROM the oxidative degradations described in Part I1 (J., 1952, 3958), it was concluded that griseofulvin possesses a benzenoid ring (A) and a hydroaromatic six-membered ring (c) thereby confirming the views of Oxford, Raistrick, and Simonart (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1967
1967
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…1) was proposed by GROVE (1952). Recently, CROSSE et al ( 1964) reported a large number of griseofulvin relatives with enhanced in vitro activity.…”
Section: Griseofulvin Floyd M Hubermentioning
confidence: 92%
“…1) was proposed by GROVE (1952). Recently, CROSSE et al ( 1964) reported a large number of griseofulvin relatives with enhanced in vitro activity.…”
Section: Griseofulvin Floyd M Hubermentioning
confidence: 92%
“…Griseofulvin (Fulvicin®, Grifulvin V®, Grisovin FP®, Gristatin®) was one of the first antifungal natural products discovered in filamentous fungi (Grove et al 1952). The drug is derived from the mold Penicillium griseofulvum and is commonly used to treat fungal infections of the skin, hair, and nails.…”
Section: Griseofulvinmentioning
confidence: 99%
“…Since then fungal microorganisms became a hunting ground for novel drug leads (Strobel and Daisy 2003;Larsen et al 2005). In the following years several further antimicrobial agents of fungal origin such as griseofulvin (Grove et al 1952) and cephalosporin C (Newton and Abraham 1955) were discovered. This stimulated pharmaceutical companies to sample and screen large collections of fungal strains especially for antibiotics (Butler 2004).…”
Section: Introductionmentioning
confidence: 99%
“…103 Earlier work by Grove had already identied the antifungal properties of 9 when he showed that griseofulvin and the so called 'curling factor' isolated from P. janczewskii were identical. Macmillan also reported one of the very rst examples of precursor-directed biosynthesis when he fed chloride-starved cultures of P. griseofulvum with KBr and isolated bromogriseofulvin.…”
Section: Griseofulvinmentioning
confidence: 99%